Question
upstudy study bank question image url

3. Using synthetic division find the quotient and the remainder when i) \( x^{3}-2 x^{2}+9 \) is divided by \( (x+2) \) \( \begin{array}{llll}\text { iii) } 4 x^{7}+3 \text { is divided by } x-3 & \text { i) } x^{4}-2 x^{3}-3 x^{2}-4 x-8 \text { is divided by } x-2\end{array} \) 4. Factorize each of the following polynomials: \( \begin{array}{llll}\text { i) } x^{3}-2 x^{2}-5 x+6 & \text { ii) } x^{4}-1 & \text { iii) } x^{4}-2 x^{3}+x-2\end{array} \)

Ask by Hammond Weaver. in Zambia
Feb 14,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

**Synthetic Division Results:** - \( x^{3}-2x^{2}+9 \) divided by \( (x+2) \): Quotient \( x^{2}-4x+8 \), Remainder \( -7 \) - \( 4x^{7}+3 \) divided by \( (x-3) \): Quotient \( 4x^{6}+12x^{5}+36x^{4}+108x^{3}+324x^{2}+975 \), Remainder \( 975 \) - \( x^{4}-2x^{3}-3x^{2}-4x-8 \) divided by \( (x-2) \): Quotient \( x^{3}-3x-10 \), Remainder \( -16 \) **Factorizations:** - \( x^{3}-2x^{2}-5x+6 = (x + 2)(x - 1)(x - 3) \) - \( x^{4}-1 = (x - 1)(x + 1)(x^{2} + 1) \) - \( x^{4}-2x^{3}+x-2 = (x + 1)(x - 2)(x^{2} + ax + b) \) (further factorization needed for the quadratic).

Solution

Solve the equation by following steps: - step0: Solve for \(x\): \(x^{4}-1=0\) - step1: Move the constant to the right side: \(x^{4}=0+1\) - step2: Remove 0: \(x^{4}=1\) - step3: Simplify the expression: \(x=\pm \sqrt[4]{1}\) - step4: Simplify: \(x=\pm 1\) - step5: Separate into possible cases: \(\begin{align}&x=1\\&x=-1\end{align}\) - step6: Rewrite: \(x_{1}=-1,x_{2}=1\) Solve the equation \( x^{3}-2 x^{2}-5 x+6=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(x^{3}-2x^{2}-5x+6=0\) - step1: Factor the expression: \(\left(x-3\right)\left(x-1\right)\left(x+2\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-3=0\\&x-1=0\\&x+2=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=3\\&x=1\\&x=-2\end{align}\) - step4: Rewrite: \(x_{1}=-2,x_{2}=1,x_{3}=3\) Solve the equation \( 4 x^{7}+3=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(4x^{7}+3=0\) - step1: Move the constant to the right side: \(4x^{7}=0-3\) - step2: Remove 0: \(4x^{7}=-3\) - step3: Divide both sides: \(\frac{4x^{7}}{4}=\frac{-3}{4}\) - step4: Divide the numbers: \(x^{7}=-\frac{3}{4}\) - step5: Simplify the equation: \(\sqrt[7]{x^{7}}=\sqrt[7]{-\frac{3}{4}}\) - step6: Calculate: \(x=\sqrt[7]{-\frac{3}{4}}\) - step7: Simplify the root: \(x=-\frac{\sqrt[7]{96}}{2}\) Solve the equation \( x^{4}-2 x^{3}+x-2=0 \). Solve the equation by following steps: - step0: Solve for \(x\): \(x^{4}-2x^{3}+x-2=0\) - step1: Factor the expression: \(\left(x-2\right)\left(x+1\right)\left(x^{2}-x+1\right)=0\) - step2: Separate into possible cases: \(\begin{align}&x-2=0\\&x+1=0\\&x^{2}-x+1=0\end{align}\) - step3: Solve the equation: \(\begin{align}&x=2\\&x=-1\\&x \notin \mathbb{R}\end{align}\) - step4: Find the union: \(\begin{align}&x=2\\&x=-1\end{align}\) - step5: Rewrite: \(x_{1}=-1,x_{2}=2\) Solve the equation \( x^{3}-2 x^{2}+9=0 \). Solve the equation(The complex numbers system) by following steps: - step0: Solve for \(x\) in the complex numbers system: \(x^{3}-2x^{2}+9=0\) - step1: Calculate: \(\begin{align}&x\approx -1.584544\\&x\approx 1.792272+1.570869i\\&x\approx 1.792272-1.570869i\end{align}\) - step2: Rewrite: \(x_{1}\approx 1.792272-1.570869i,x_{2}\approx 1.792272+1.570869i,x_{3}\approx -1.584544\) - step3: Remove the complex number(s): \(x\approx -1.584544\) Solve the equation \( x^{4}-2 x^{3}-3 x^{2}-4 x-8=0 \). Solve the equation(The complex numbers system) by following steps: - step0: Solve for \(x\) in the complex numbers system: \(x^{4}-2x^{3}-3x^{2}-4x-8=0\) - step1: Calculate: \(\begin{align}&x\approx 3.419492\\&x\approx -0.040039-1.321014i\\&x\approx -0.040039+1.321014i\\&x\approx -1.339414\end{align}\) - step2: Rewrite: \(x_{1}\approx -1.339414,x_{2}\approx -0.040039+1.321014i,x_{3}\approx -0.040039-1.321014i,x_{4}\approx 3.419492\) - step3: Remove the complex number(s): \(x_{1}\approx -1.339414,x_{2}\approx 3.419492\) Let's solve the problems step by step. ### 3. Synthetic Division #### i) \( x^{3}-2x^{2}+9 \) divided by \( (x+2) \) To perform synthetic division, we will use the root of \( x + 2 = 0 \), which is \( x = -2 \). 1. Write the coefficients of the polynomial: \( 1, -2, 0, 9 \) (note that the coefficient of \( x \) is 0). 2. Set up synthetic division: ``` -2 | 1 -2 0 9 | -2 8 -16 --------------------- 1 -4 8 -7 ``` The bottom row gives us the coefficients of the quotient and the remainder: - Quotient: \( x^{2} - 4x + 8 \) - Remainder: \( -7 \) #### iii) \( 4x^{7}+3 \) divided by \( x-3 \) Using \( x = 3 \): 1. Write the coefficients: \( 4, 0, 0, 0, 0, 0, 3 \). 2. Set up synthetic division: ``` 3 | 4 0 0 0 0 0 3 | 12 36 108 324 972 --------------------------- 4 12 36 108 324 975 ``` The bottom row gives us: - Quotient: \( 4x^{6} + 12x^{5} + 36x^{4} + 108x^{3} + 324x^{2} + 975 \) - Remainder: \( 975 \) #### ii) \( x^{4}-2x^{3}-3x^{2}-4x-8 \) divided by \( x-2 \) Using \( x = 2 \): 1. Write the coefficients: \( 1, -2, -3, -4, -8 \). 2. Set up synthetic division: ``` 2 | 1 -2 -3 -4 -8 | 2 0 -6 -8 ------------------------- 1 0 -3 -10 -16 ``` The bottom row gives us: - Quotient: \( x^{3} - 3x - 10 \) - Remainder: \( -16 \) ### 4. Factorization #### i) \( x^{3}-2x^{2}-5x+6 \) Using the roots found earlier: - Roots: \( x_{1} = -2, x_{2} = 1, x_{3} = 3 \) Thus, the factorization is: \[ (x + 2)(x - 1)(x - 3) \] #### ii) \( x^{4}-1 \) This is a difference of squares: \[ x^{4}-1 = (x^{2}-1)(x^{2}+1) = (x-1)(x+1)(x^{2}+1) \] #### iii) \( x^{4}-2x^{3}+x-2 \) Using the roots found earlier: - Roots: \( x_{1} = -1, x_{2} = 2 \) Thus, the factorization is: \[ (x + 1)(x - 2)(x^{2} + ax + b) \] To find \( a \) and \( b \), we can use polynomial long division or synthetic division to find the quadratic factor. ### Summary of Results 1. **Synthetic Division Results:** - \( x^{3}-2x^{2}+9 \) by \( (x+2) \): Quotient \( x^{2}-4x+8 \), Remainder \( -7 \) - \( 4x^{7}+3 \) by \( (x-3) \): Quotient \( 4x^{6}+12x^{5}+36x^{4}+108x^{3}+324x^{2}+975 \), Remainder \( 975 \) - \( x^{4}-2x^{3}-3x^{2}-4x-8 \) by \( (x-2) \): Quotient \( x^{3}-3x-10 \), Remainder \( -16 \) 2. **Factorizations:** - \( x^{3}-2x^{2}-5x+6 = (x + 2)(x - 1)(x - 3) \) - \( x^{4}-1 = (x - 1)(x + 1)(x^{2} + 1) \) - \( x^{4}-2x^{3}+x-2 = (x + 1)(x - 2)(x^{2} + ax + b) \) (further factorization needed for the quadratic).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find the quotient and remainder using synthetic division for the given polynomials: **i)** For \( x^3 - 2x^2 + 9 \) divided by \( x + 2 \): - Using synthetic division with -2: ``` -2 | 1 -2 0 9 | -2 8 -16 --------------------- 1 -4 8 -7 ``` The quotient is \( x^2 - 4x + 8 \) and the remainder is \(-7\). **iii)** For \( 4x^7 + 3 \) divided by \( x - 3 \): - Using synthetic division with 3: ``` 3 | 4 0 0 0 0 0 0 3 | 12 36 108 324 972 2916 ------------------------------ 4 12 36 108 324 972 2919 ``` The quotient is \( 4x^6 + 12x^5 + 36x^4 + 108x^3 + 324x^2 + 972x + 2919 \) and the remainder is 0. For factorization: **i)** \( x^3 - 2x^2 - 5x + 6 \): - By testing for roots, \( x = 3 \) is a root. Using synthetic division: ``` 3 | 1 -2 -5 6 | 3 3 -6 -------------------- 1 1 -2 0 ``` The polynomial factors to \( (x - 3)(x^2 + x - 2) \), which further factors to \( (x - 3)(x - 1)(x + 2) \). **ii)** \( x^4 - 1 \): - This can be factored as a difference of squares: \[ x^4 - 1 = (x^2 - 1)(x^2 + 1) = (x - 1)(x + 1)(x^2 + 1). \] **iii)** For \( x^4 - 2x^3 + x - 2 \): - Testing \( x = 2 \) gives us: ``` 2 | 1 -2 0 1 -2 | 2 0 2 0 ---------------------- 1 0 0 3 0 ``` So, it factors to \( (x - 2)(x^3 + 3) \) which can also be rewritten and factored further. If you're stuck on how to factor or perform synthetic division, just remember: practice makes perfect, and don't be afraid to ask for help! Keep it fun, and math will start to click!

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy